2016
DOI: 10.1111/ans.13762
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of staging laparoscopy in a subset of biliary cancers: a meta‐analysis

Abstract: This meta-analysis revealed that 32.4% of patients with HC and 27.6% of patients with GBC may avoid unnecessary laparotomy with the use of SL. It is worthwhile to perform SL combined with an intraoperative ultrasound in patients with suspected GBC or HC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…624 Positive staging laparoscopy (SL) prevents unnecessary invasive operations that are associated with greater in-hospital mortality and prolonged length of stay. 9,25 Multiple reports demonstrate a uniformly poor prognosis in gastric cancer patients with peritoneal disease, leading the National Comprehensive Cancer Network (NCCN) to recommend pretreatment SL for patients with clinical stage IB or higher disease.…”
mentioning
confidence: 99%
“…624 Positive staging laparoscopy (SL) prevents unnecessary invasive operations that are associated with greater in-hospital mortality and prolonged length of stay. 9,25 Multiple reports demonstrate a uniformly poor prognosis in gastric cancer patients with peritoneal disease, leading the National Comprehensive Cancer Network (NCCN) to recommend pretreatment SL for patients with clinical stage IB or higher disease.…”
mentioning
confidence: 99%
“…16 In a recent metaanalysis (2017) comprising eight studies and 1062 patients undergoing SL for biliary cancer, the yield in GBC and HC was found to be 27.6% and 32.4%, respectively. 17 In this study, we found that the utilization of SL for EHBT increased across 10 tertiary centers over the 15-year time period and was significantly higher in GBC than DC or HC. Yet, the yield of SL overall was modest in comparison to prior studies (16.8%) and did not significantly change over time or between biliary cancer subtypes.…”
Section: Resultsmentioning
confidence: 55%
“…The authors further suggested that improvements in SL could be made with the inclusion of laparoscopic ultrasound for deep parenchymal liver lesions and/or endoscopic or laparoscopic sampling of interaortocaval lymph nodes . In a recent meta‐analysis (2017) comprising eight studies and 1062 patients undergoing SL for biliary cancer, the yield in GBC and HC was found to be 27.6% and 32.4%, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between the T stage of GBC and the beneit of diagnostic laparoscopy is not yet established in cholangiocarcinomas [37], most researchers suggest the use of diagnostic laparoscopy in patients with T2/3 lesions scheduled for reresection [38,39], in order to save them the burden of a full laparotomy. A recent meta-analysis found the accuracy of diagnostic laparoscopy to be 63.9% [40]. The sensitivity of diagnostic laparoscopy in GBC was 0.642 (95% CI: 0.579-0.7).…”
Section: Updates In Gallbladder Diseasesmentioning
confidence: 99%